Whey protein isolate protects against cyclophosphamide-induced acute liver and kidney damage in rats - Dina F. Mansour, Abeer A. A. Salama, Rehab R. Hegazy, Enayat A. Omara, Somaia A. Nada (Journal of Applied Pharmaceutical Science, 2017)
Cyclophosphamide (CP), a common chemotherapy, interferes with the antioxidant systems of vital organs. This study investigated the protective effects of whey protein isolate (WPI) against CP-induced acute liver and kidney damage in rats. Forty adult Wistar rats were allocated into five groups. The first received the vehicles and acted as normal control. In the other groups, rats were injected with a single intraperitoneal dose of CP (200 mg/kg). The last three groups were pre-treated with oral WPI at doses of 75, 150 or 300 mg/kg/day, respectively, for 15 successive days. Forty-eight hours following CP injection, animals were investigated for serum alanine transaminase, aspartate transaminase, urea and creatinine levels, as well as hepatic and renal reduced glutathione, malondialdehyde, nitrite, interleukin 1β, and myeloperoxidase contents. Histopathological examination as well as immunohistochemical detection of cyclooxygenase-2 in liver and kidney were conducted. CP induced organ dysfunction, oxidative stress, inflammation, and histopathological alterations in liver and kidney. WPI significantly protected against CP-induced deterioration of liver and kidney functions showing marked dose-dependent anti-oxidant and anti-inflammatory properties demonstrated by the biochemical, immunohistochemical and histopathological results. In conclusion, the study reveals the protective effects of WPI against CP-induced acute liver and kidney damage via antioxidant and anti-inflammatory mechanisms.
Keywords: Cyclophosphamide, whey protein isolate, oxidative stress, inflammation,liver, kidney, rat.